THE ROLE OF LOVE OF MONEY, THE UNDERSTANDING OF TAX, AND TAX SANCTION ON TAX EVASION – TRI PANTANGAN AS MODERATING VARIABLE - Sri Ayem; Fuadhillah Kirana Putri; Cia Zulviatul Azkiah (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2026)
This study examines the effect of love of money, understanding of tax law, and tax sanctions on tax evasion in Yogyakarta City with Tri Pantangan as a moderating variable. Tri Pantangan is a teaching concept by the Father of Indonesian Education, Ki Hadjar Dewantara. This concept includes three prohibitions: prohibition from abuse of power, financial violations, and immoral behaviour. Understanding and complying with these prohibitions can influence taxpayers' behaviour toward understanding tax laws and encourage compliance through moral teachings. Therefore, Tri Pantangan, in terms of tax evasion behaviour compliance, is the reason for being a moderating variable in this study. Data was collected using a convenience sampling technique, generating 45 respondents as the sample. The findings of data analysis using SPSS version 23 show that Tax evasion has negative significant influences on love of money. Understanding of tax law has positive effect on tax evasion. Tax Sanction significantly positively affects the Tax Evasion. Tri Pantangan moderates the relationship between love of money and tax evasion, reinforcing the negative influence of love of money on tax evasion. Tri Pantangan is unable to moderate the relationship between understanding tax law and tax evasion. Tri Pantangan does not moderate the relationship between tax sanction and tax evasion. The result of this study can be beneficial for tax authorities to formulate more effective tax policies in tightening tax sanctions and integrate Tri Pantangan into tax socialization as well as character education programs as informal efforts to reduce the intention to commit tax evasion.